(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2017)
Considering the modern conditions of RA socio-economic development and strategic reasons, socio-economic development of contiguous areas and strengthening the defensibility of the country has a special importance. Based on the analysis of statistical data, the tendencies of RA frontier areas settlement dynamics (of population and settlements) over the last 3 decades and the problems connected with those tendencies have been revealed in the article.